(untitled) (Editora Impacto Científico, 2025)
This article analyzes the Re-Saber Program, established by MEC Ordinance No. 24 of January 19, 2021. The analysis of the legal framework of Re-Saber does not commit to raising the educational level of participants and relegates to a secondary position the articulation of experiential knowledge with scientific knowledge for the population destined for the most precarious work, underemployment, informality, and outsourcing. In this sense, the Re-Saber Program, by making training more precarious, contributes to the dismantling of access, retention, and academic success, while co-opting education workers into this project under the guise of being efficient, flexible, and amplifying the professional/individual status of its base team; and, lastly, it takes advantage of this opportunity to increase statistics on certification in institutions (number of enrolled students, certificates, etc.), under the pretext that there is a commitment from the State to education and to workers. DOI: https://doi.org/10.56238/edimpacto2025.092-072